1995
DOI: 10.1007/bf00133486
|View full text |Cite
|
Sign up to set email alerts
|

Differences in proliferation and invasion by normal, transformed and NF1 Schwann cell cultures are influenced by matrix metalloproteinase expression

Abstract: Loss of negative growth regulation and high invasive potential are neoplastic traits often associated with abnormal expression of matrix metalloproteinases (MMPs). We previously found MMP-3 (stromelysin/transin) was secreted by quiescent rat Schwann cell cultures and expressed potent antiproliferative activity. In the present study we observed that human Schwann cells and cutaneous neurofibroma Schwann cell cultures secreted abundant MMP-3 and their proliferation was inhibited by autologous and rat Schwann cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Tissues from rat mammary carcinomas, known to express activated c-H-ras, show increased MMP production compared to normal breast tissue (5). In recent studies, Schwann cells derived from neurofibromas have been shown to secrete high levels of MMP-1 (collagenases) and MMP-9 (gelatinase B) and also to invade a collagen barrier resembling basement membranes (44). It has been suggested that increased Ras activity in neurofibromaderived Schwann cells might be responsible for the invasiveness of the cells through stimulation of MMP production.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues from rat mammary carcinomas, known to express activated c-H-ras, show increased MMP production compared to normal breast tissue (5). In recent studies, Schwann cells derived from neurofibromas have been shown to secrete high levels of MMP-1 (collagenases) and MMP-9 (gelatinase B) and also to invade a collagen barrier resembling basement membranes (44). It has been suggested that increased Ras activity in neurofibromaderived Schwann cells might be responsible for the invasiveness of the cells through stimulation of MMP production.…”
Section: Discussionmentioning
confidence: 99%
“…57,88 This Schwann cell, which lacks functional neurofibromin, has a substantial growth advantage 77 and a loss of negative autocrine growth control. 76 The stage of differentiation of the Schwann cell as the progenitor cell for NF1 tumors is still the subject of some debate. 53,61 In 2009, Le and coworkers 61 proposed that the neural crest stem cell is the cell of origin for cutaneous neurofibromas after identifying a population of stem/progenitor cells residing in the dermis (called skin-derived precursors) that, through loss of NF1, form neurofibromas.…”
Section: Neurofibromasmentioning
confidence: 99%
“…36 Candidates include expression of epidermal and vascular endothelial growth factors and their receptors and matrix metalloproteinases. 37,38 Normal cellular relationships within the perineurium are contingent upon closely regulated signalling between Schwann cells, axons, fibroblasts and perineurial cells. Impaired signalling between the components of neurofibromas might promote neurofibroma development.…”
Section: Pathogenesis Of Neurofibromasmentioning
confidence: 99%